Design of Exercise Device for Older Adults - Gallegos Barría, Daniel; Amador Cáceres, Belkys; Martínez Bordes, Gabriela; San Martín Correa, Mauricio (Revista Mexicana de Ingenieria Biomedica, 2023)
Older adults should perform physical activity to improve cardiorespiratory functions. Aerobic exercises improve cardiovascular function, decrease basal heart rate and blood pressure, and improve mood and energy. To facilitate the execution of aerobic physical activity in older adults, the objective of this research was to design an exercise device for older adults. Starting from design specifications such as comfort, size, weight, resistance, and cost, we developed the detailed design of a horizontal bicycle. The designed device, thanks to its horizontally disposed structure, its adequate resistance to pedaling, its dimensioning based on anthropometric measurements of the Chilean population, and the disposition of sensors for heart rate and oxygen saturation, is suitable for older adults. Its weight and size also make it convenient for use inside the home, and the use of materials, components, and manufacturing processes available nationally and within the cheapest options, increases the possibility of access by older adults.